Suppression of Physaria fendleri SDP1 Increased Seed Oil and Hydroxy Fatty Acid Content While Maintaining Oil Biosynthesis Through Triacylglycerol Remodeling - Azeez, Abdul; Parchuri, Prasad; Bates, Philip D. (Frontiers in Plant Science, 2022)
Physaria fendleri is a burgeoning oilseed crop that accumulates the hydroxy fatty acid (HFA), lesquerolic acid, and can be a non-toxic alternative crop to castor for production of industrially valuable HFA. Recently, P. fendleri was proposed to utilize a unique seed oil biosynthetic pathway coined “triacylglycerol (TAG) remodeling” that utilizes a TAG lipase to remove common fatty acids from TAG allowing the subsequent incorporation of HFA after initial TAG synthesis, yet the lipase involved is unknown. SUGAR DEPENDENT 1 (SDP1) has been characterized as the dominant TAG lipase involved in TAG turnover during oilseed maturation and germination. Here we characterized the role of a putative PfeSDP1 in both TAG turnover and TAG remodeling. In vitro assays confirmed that PfeSDP1 is a TAG lipase and demonstrated a preference for HFA-containing TAG species. Seed-specific RNAi knockdown of PfeSDP1 resulted in a 12-16% increase in seed weight and 14-19% increase in total seed oil content with no major effect on seedling establishment. The increase in total oil content was primarily due to ~4.7% to ~14.8% increase in TAG molecular species containing two HFA (2HFA-TAG), and when combined with a smaller decrease in 1HFA-TAG content the proportion of total HFA in seed lipids increased 4-6%. The results are consistent with PfeSDP1 involved in TAG turnover but not TAG remodeling to produce 2HFA-TAG. Interestingly, the concomitant reduction of 1HFA-TAG in PfeSDP1 knockdown lines suggests PfeSDP1 may have a role in reverse TAG remodeling during seed maturation that produces 1HFA-TAG from 2HFA-TAG. Overall, our results provide a novel strategy to enhance the total amount of industrially valuable lesquerolic acid in P. fendleri seeds.